Education and Assessment of Foot Health Status to Prevent Diabetic Ulcers - Suciana, Fitri; Rayasari, Fitriyan; Anggraini, Dewi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Lifestyle changes and urbanization are important causes of health problems, especially diabetes mellitus and have continued to increase throughout this millennium. Diabetes mellitus is listed as the sixth leading cause of death in the world. If prevention and treatment is not carried out, diabetes mellitus can cause complications. One complication can be diabetic ulcers. Prevention of diabetic ulcers can be done, among other things, by evaluating the feet and the shape of the feet so that they can determine appropriate footwear, examining the feet and legs, checking the pulse, and assessing the strength of the feet. The aim of this research is to determine the effectiveness of education and assessing foot health status in preventing the occurrence of diabetic ulcers. The method uses a quasi-experimental design. The population in this study was 30 posyandu cadres in Dukuh Village, Bayat District. The sampling technique in this research was the Total Sampling method. Instruments using leaflets for conducting education and HFSQ questionnaires for assessing foot health status. Data were tested using the Mann Whitney test. The result is a P value of 0.00, which means there is a difference in the average foot health status score after being given education about foot care. The average pretest score was 16.84, increasing to 18.15. The conclusion is that education can change foot care behavior by assessing foot health status.